Effects of Social Attachment on Experimental Drug Use From Childhood to Adolescence: An 11-Year Prospective Cohort Study - Chiang, Yi-Chen; Li, Xian; Lee, Chun-Yang; Wu, Chi-Chen; Chang, Hsing-Yi; Zhang, Shuoxun (Frontiers in Public Health, 2022)
Background Drug use among adolescents are still crucial issues that endanger their lifetime health. Evidence concerning the interpersonal-related factors influencing youngsters' experimental drug use behavior, especially from longitudinal and school-based prospective cohort studies, is insufficient. We aimed to describe the annual incidence rate and mean annual incidence rate of experimental drug use from childhood to adolescence by education stage, clarify the risk in childhood and examine the longitudinal relationship between social attachment factors and experimental drug use. Materials and Methods The data were derived from the 1st to 11th wave of the longitudinal study. In total, 1,106 respondents aged 19–20-year-old were followed up for 11 years (from 9 to 10-year-old) in Taiwan. A survival analysis was used to analyze the time-invarying/time-dependent effects of social attachment factors on experimental drug use. Results The mean annual incidence rate of experimental drug use from childhood to adolescence was 6.8‰. The incidence increased over time and was the highest in the first year of university (19.3‰). Boys were more likely to use drugs than girls. A low degree of self-perceived likeability in childhood was a risk factor influencing experimental drug use. On average, a low degree of parental supervision and a high degree of family conflict were both influential risk factors. According to the time-dependent models, a high degree of parental supervision, a high degree of family support and a low degree of family conflict in the current year can protect children and adolescents from drug use, whereas a sustained low degree of parental supervision and a high degree of family conflict may promote students' experimental drug use. Conclusion Parents should be informed and educated to avoid family conflict during childhood, maintain consistent supervision of their children's behavior, provide adequate family support, and pay attention to their children's interpersonal relationships in school. Teachers should focus on the social attachment status of their students while considering their attachments to their families and peers.